Changes in n-alkane distribution of the Tianshui Basin and its links to the Tibetan plateau uplift and global climate change - Li, Xiaomiao; Peng, Tingjiang; Han, Churun; Liu, Zhichao; Ma, Zhenhua; Li, Meng; Song, Chunhui (Frontiers in Earth Science, 2023)
The Neogene fluvial-lacustrine sediments of the Tianshui Basin provide records of the interactions among tectonic activity, climatic and ecological change on the northeastern Tibetan Plateau (NE TP), from ~12.4 to 2.6 Ma. We investigated the n-alkanes record of a sedimentary sequence from the Tianshui Basin which reveals shifts in the productivity and sources of n-alkanes. The productivity of n-alkanes doubled many times during ~4.2-3.2 Ma, accompanied by the increased contribution from aquatic plants; additionally, non-emergent macrophytes occurred sporadically after ~4.2 but became a significant n-alkanes source after ~3.2 Ma. Changes in the inferred Late Miocene ecology of the region are consistent with a major climate transition in response to global cooling. The oscillations of the types and concentrations of n-alkanes during 4.2-3.2 Ma were likely related to the evolution of the East Asian monsoon (EAM), driven by the tectonic uplift of the NE TP and global cooling. The major increase in aquatic plants and biological productivity of this region at ~3.2 Ma may have been caused by the strengthening of the East Asian summer monsoon (EASM) and regional tectonic uplift.